Composite A-type molecular sieve raw material powder containing radio wave absorbing material, all-zeolite molecular sieve, their manufacturing method and use
The introduction of micro-nano-sized radio wave absorbing materials into A-type molecular sieve synthesis enhances the stability and efficiency of the molecular sieve, effectively addressing the challenges of impurity removal and regeneration in lithium-ion nonaqueous electrolytes.
Patent Information
- Application Number
- JP2023546136
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-03
- Filing Date
- 2021-11-17
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2041-11-17
AI Technical Summary
Existing methods for producing Li-LSX molecular sieves are complex and result in poor hydrothermal stability, leading to ineffective removal of impurities in lithium-ion nonaqueous electrolytes.
A composite A-type molecular sieve raw powder containing micro-nano-sized radio wave absorbing materials is synthesized using microwave heating, which enhances the efficiency and stability of the molecular sieve, allowing for effective adsorption and regeneration of impurities.
The composite A-type molecular sieve with radio-absorbing materials achieves high efficiency in adsorbing small molecular impurities like water from lithium-ion nonaqueous electrolytes, with rapid regeneration by microwave heating, reducing energy consumption and extending the molecular sieve's lifespan.
Abstract
Description
[Technical field]
[0001] The present invention relates to the technology in the field of molecular sieves, in particular to a composite A-type molecular sieve raw material powder containing radio wave absorbing material, an all-zeolite molecular sieve, and the preparation methods and uses thereof. [Background technology]
[0002] Lithium ion batteries are mainly composed of a positive electrode, a negative electrode, and an electrolyte. Charging and discharging cannot be performed without the intercalation and disengagement of lithium ions between the positive and negative electrodes via the electrolyte. During the first charge and discharge of a lithium ion battery, a reaction occurs between the electrolyte and the electrode material, forming a solid electrolyte interfacial membrane (SEI), which has an important effect on the characteristics of the lithium ion battery. However, impurities such as traces of water, acids, and alcohols are inevitably mixed into the electrolyte during the production process. Even in commercial electrolytes with excellent characteristics, the content of these impurities is about 0.001%, but these trace impurities can destroy or change the properties of the SEI membrane, reducing the reversible capacity and cycle characteristics of the battery. In addition, traces of water can decompose the lithium hexafluorophosphate salt in the electrolyte and react with the organic solvent in the electrolyte to produce alcohol. Furthermore, they consume lithium ions during charging and discharging of the lithium ion battery, converting them into LiOH, Li 2 The purity of the electrolyte has a significant impact on the electrochemical properties of lithium-ion batteries.
[0003] Molecular sieves are highly hygroscopic and have excellent properties that allow them to be used to dehydrate almost all types of solvents, and are therefore widely used in laboratories and industries. Lithium ion nonaqueous electrolytes can be produced by using theoretically appropriate molecular sieves as raw materials to produce lithium-type molecular sieves, which can efficiently remove trace amounts of water and small molecular impurities such as hydrogen fluoride and methanol that are close to the molecular size of water.
[0004] Patent Document 1: Patent application CN200810050070.2 (2008) discloses a method for producing Li-LSX molecular sieve, which involves exchanging LSX with potassium ion aqueous solution multiple times to produce K + -LSX was obtained, which was then exchanged multiple times with an aqueous ammonium ion solution to give NH 4 -LSX is obtained, and finally Li-LSX is obtained by lithium ion exchange. During the lithium ion exchange process, NH 3 It is necessary to recover the Li to promote Li exchange. 4 + Although the Li utilization rate is increased by adopting the transition exchange method, the process flow is relatively complicated, and the molecular sieve framework itself has poor hydrothermal stability, so that frequent hydrothermal ion exchange may destroy the molecular sieve framework, and as a result, the finished product may not be usable for removing impurities from lithium ion non-aqueous electrolyte. Another reason why the Li-LSX produced in this application cannot be used for removing impurities from lithium ion non-aqueous electrolyte is related to the production of raw molecular sieve powder. In practical use, the raw molecular sieve powder often cannot be used normally unless it is made into small spheres by a spheroidization process. In the spheroidization process, it is unavoidable to add binders and other additives, so that even if the Li exchange degree is high in the previous stage, the lithium ion content will inevitably decrease after the spheroidization process. In addition, when the lithium ion non-aqueous electrolyte highly adsorbs a small amount of water, it will cause secondary contamination of other ions due to ion exchange in materials such as binders, and in particular, sodium ion contamination is fatal to the lithium ion non-aqueous electrolyte.
[0005] In addition to the above problems, in the process of removing impurities from a large amount of lithium-ion nonaqueous electrolyte, there are also problems of how to efficiently desorb and regenerate the molecular sieve that has adsorbed impurities, and how to reduce the manufacturing cost of the adsorbent.
[0006] The present invention has been completed in order to solve the above problems existing in the prior art. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent application CN200810050070.2 Summary of the Invention [Problem to be solved by the invention]
[0008] Among many types of molecular sieves, A-type molecular sieves are easy to manufacture, low cost, and can be exchanged with various ions to obtain 3A, 4A, and 5A molecular sieves, which can achieve the sieving, separation, and adsorption effects of molecules of various sizes. In view of this, the present invention proposes a composite A-type molecular sieve raw material powder containing radio wave absorbing material, an all-zeolite molecular sieve, their manufacturing methods, and uses in response to the above-mentioned shortcomings in the prior art, and the manufactured all-zeolite molecular sieve can highly adsorb specific molecules, can be rapidly regenerated by microwave heating, and can improve the activation and regeneration efficiency. [Means for solving the problem]
[0009] A first aspect of the present invention provides a composite A-type molecular sieve raw material powder containing a radio wave absorbing material, the raw material powder including a micro-nano-sized radio wave absorbing material and an A-type molecular sieve grown in situ using the micro-nano-sized radio wave absorbing material as a crystal seed, the A-type molecular sieve covering the radio wave absorbing material. In some embodiments, the micro-nano sized radio wave absorbing material comprises one or more of silicon carbide particles, silicon carbide fibers, carbon fibers, graphene, carbon nanotubes, and carbon black, and the A type molecular sieve is one of LTA (Linde Type A) type molecular sieves, typically, for example, 3A molecular sieve, 4A molecular sieve, and 5A molecular sieve.
[0010] The size of the radio wave absorbing material is preferably 1 nm to 100 μm, and more preferably 10 nm to 10 μm.
[0011] A second aspect of the present invention is Weigh out the micro-nano-sized radio wave absorbing material powder and add it to the A-type molecular sieve precursor reaction solution, then heat it with microwaves to react; When heated by microwaves, the radio wave absorbing material is selectively heated, and the molecular sieve grows in situ as a crystal seed for growing due to the effect of the particle surface, to synthesize the A-type molecular sieve, and the synthesized A-type molecular sieve covers the radio wave absorbing material; After the reaction is completed, the mixture is dried to obtain a raw powder of the composite A-type molecular sieve containing the radio wave absorbing material.
[0012] In some embodiments, the A-type molecular sieve precursor reaction solution is an alkaline silica aluminum reaction solution, and the molar ratio of the composition of the reaction solution materials is xM 2 O:ySiO 2 :Al 2 O 3 :zH 2 O (wherein M is one or more of an alkali metal ion and an organic ammonium ion, x is 2 to 12, y is 1.5 to 6.5, and z is 30 to 400), the microwave heating output power is 0.1 to 2 kW, the reaction temperature is 40 to 110° C., the reaction time is 1 to 48 hours, and the drying temperature is 80 to 120° C. Preferably, the heating temperature is 60 to 100° C., and the reaction time is 1 to 24 hours.
[0013] A third aspect of the present invention is A molding step S1 in which a composite A-type molecular sieve raw material powder containing an electromagnetic wave absorbing material and a binder are uniformly mixed in a predetermined ratio, milled, molded in a granulator, and then dried and roasted to obtain a molded particle material; The molded particle material obtained in step S1 is baked and put into an alkaline solution, and then heated to carry out a crystallization reaction, so that the binder in the molded particle material is converted into zeolite crystals to obtain an all-zeolite molecular sieve; and a crystal transformation step S2. Step S3 of ion exchange: the all-zeolite molecular sieve produced in step S2 is humidified and immersed in water, then sent into an ion exchange column by a peristaltic pump, heated to an ion exchange temperature, and then introduced with a target ion solution to carry out ion exchange; after the ion exchange reaction is completed, the all-zeolite molecular sieve is rinsed with deionized water, further dehydrated, and the target ion solution modified all-zeolite molecular sieve is collected; and an activation step S4 of subjecting the target ion solution modified all-zeolite molecular sieve produced in step S3 to a pre-baking treatment, sending the semi-finished product after the pre-baking to an activation furnace for roasting, and cooling the semi-finished product to a discharge temperature after the roasting is completed, and discharging the semi-finished product, and optionally sieving the semi-finished product under the protection of nitrogen or dry air to obtain a finished all-zeolite molecular sieve containing the radio wave absorbing material.
[0014] Preferably, the weight percentage of the binder in the shaped particle material is 5% to 20%, and the binder is one or more of kaolin, halloysite, and allophane.
[0015] In step S1, one or more additives are further added to optimize various properties of the molded particle material, such as improving strength, reducing wear, improving porosity, etc., and the additives include one or more of water glass, aluminum sol, silica sol, silicone resin emulsion, pyrophosphate, aluminum hydrogen phosphate, cellulose and its derivatives, tannin extract, etc. The shape of the molded particles may be spherical, strand-like, etc., and should be designed according to the specific application.
[0016] In step S2, the alkaline solution is at least one of a sodium hydroxide solution, a potassium hydroxide solution, and a calcium hydroxide solution, the concentration of the solution is 1% by mass to 40% by mass, preferably 1% by mass to 15% by mass, and the heating temperature is 65 to 125°C, preferably 75 to 95°C.
[0017] In step S3, the target ion solution is at least one of a soluble chloride solution, a hydroxide solution, a sulfate solution, and a nitrate solution containing the target ion solution, the concentration of the solution is 1% by mass to 40% by mass, the ion exchange temperature is 50 to 130°C, the pH value during the ion exchange is controlled in the range of 6 to 12, and the temperature of the deionized water used for rinsing is 60 to 90°C.
[0018] In step S4, the baking temperature is controlled at 80-220°C, the moisture of the product after drying is controlled at 5%-15%, and the activation furnace is preheated with dry gas, and then the target ion solution modified all-zeolite molecular sieve produced in step S3 is roasted, the preheating temperature is 400-800°C, the roasting temperature is 500-580°C, the roasting time is 3-5 hours, and the discharge temperature is 50-20°C. The dry gas is preferably pure nitrogen gas or dry compressed air with a dew point range of -50°C to -90°C.
[0019] A fourth aspect of the present invention provides an all-zeolite molecular sieve containing a radio wave absorbing material, which is produced by the above-mentioned production method, has a particle size distribution of 0.1 to 5.0 mm, an ion exchange degree in the process of 95% or more, a static moisture adsorption of 20 wt% or more, a water content of 1.5 wt% or less, and an abrasion rate of less than 1.5 wt%.
[0020] In some embodiments, the all-zeolite molecular sieve containing the radio wave absorbing material is activated and regenerated by microwave heating after adsorption. That is, after the adsorption by the molecular sieve is completed, the molecular sieve is washed, and then activated by microwave heating to dehydrate and regenerate the molecular sieve, thereby recovering the adsorption ability of the molecular sieve, thereby realizing the recycling of the molecular sieve. The output power of microwave heating is set to 0.5-2kW, and the temperature of the all-zeolite molecular sieve containing the radio wave absorbing material is increased to 100-250°C, and the activation and regeneration are completed by processing for 1-40min.
[0021] A fifth aspect of the present invention provides the use of an all-zeolite molecular sieve containing a radio wave absorbing material as an adsorbent for removing impurities, particularly for removing impurities from a lithium ion non-aqueous electrolyte.
[0022] In lithium ion non-aqueous electrolyte, the diameter of impurity molecules such as traces of water, hydrogen fluoride and methanol is approximately less than 0.4 nm, but the radius of the organic solvent molecules in the electrolyte is large, so if an all-zeolite lithium-type molecular sieve containing a radio wave absorbing material with a pore size of 4A is used, it can ensure that the organic solvent is adsorbed and not removed while removing the impurities. If an all-zeolite lithium-type molecular sieve containing a radio wave absorbing material with a pore size of 3A or 5A is used, the impurity removal effect is slightly reduced. In the above use, the use of an all-zeolite lithium-type molecular sieve containing a radio wave absorbing material can avoid secondary pollution caused by ion exchange in impurity removal. Effect of the Invention
[0023] Technical effects Compared with the prior art, the present invention has the following technical advantages: 1) By adding micro-nano materials with radio wave absorbing function, molecular sieve synthesis is promoted, the synthesis efficiency of molecular sieve is improved, composite A-type molecular sieve raw material powder containing radio wave absorbing material is synthesized, and an all-zeolite molecular sieve with high-efficiency microwave heating function is obtained. After this molecular sieve adsorbs small molecular substances such as water in the electrolyte, the adsorbed small molecular substances can be removed efficiently and with low energy consumption by microwave heating, and the heating regeneration time can be shortened from several hours to about 30 minutes, or even to several minutes, realizing efficient recycling of molecular sieves and even rapid online regeneration. Like the desorption and regeneration of other molecular sieves, the all-zeolite molecular sieve containing radio wave absorbing material can also be activated by high-temperature airflow heating, but it is difficult to play the role of radio wave absorbing material in this activation and regeneration process, and online activation cannot be realized. 2) When synthesizing the composite A-type molecular sieve raw material powder containing the radio wave absorbing material based on the surface effect of the radio wave absorbing functional material in microwave heating, there is no need to add or remove organic or inorganic template, the process is simple, and the function of the radio wave absorbing functional material is different from that of the template. 3) By granulating the molecular sieve powder, the permeability of the electrolyte during the adsorption process can be improved, and the adsorption processing efficiency can be improved. Compared to conventional powder molecular sieves, the filtration time can be shortened from the hours to the minutes. 4) By subjecting the binder added in the molding process to a crystal conversion treatment, the binder with a non-zeolite crystal structure can be converted into a zeolite crystal, thereby improving the adsorption properties of the molecular sieve, and the adsorption capacity can be improved by 5% to 20% compared with that of the non-crystal converted molecular sieve. In addition, the all-zeolite molecular sieve can be produced without repeatedly performing water-heat exchange, and the structural stability can be effectively improved. 5) The all-zeolite molecular sieve containing the radio wave absorbing material produced can fully utilize the molecular sieve's high water removal properties, simplify the water removal process, improve the efficiency of water removal, and improve the quality of the electrolyte. In addition, by using the all-zeolite lithium-type molecular sieve containing the radio wave absorbing material, Na + , K + The content of Li is extremely low, and when it adsorbs the trace amounts of water, hydrogen fluoride, methanol, and other molecules in the electrolyte, + in the electrolyte to replace the Li + The purity is not affected, and in particular no secondary contamination occurs, and the cycle characteristics of the lithium ion battery can be ensured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention will be described in detail below with reference to specific embodiments. Experimental methods for which no specific conditions are specified in the examples are carried out according to conventional methods and conditions. Example 1
[0025] This embodiment relates to a method for producing an all-zeolite lithium-type molecular sieve containing a radio wave absorbing material, including steps S1 to S5.
[0026] S1: In-situ synthesis of composite A-type molecular sieve raw powder with radio wave absorbing function Molar ratio of materials: 3Na 2 O:2SiO 2 :Al2 O 3 :128H 2 In O, sodium silicate and sodium aluminate were weighed to prepare solutions respectively, and sodium hydroxide was added to the two solutions respectively, and then the two solutions were mixed uniformly. Weigh out 1 kg of silicon carbide powder, add it to the alkaline silica aluminosol reaction liquid (added according to the theoretical yield of 9 kg of A-type molecular sieve), and place it in a microwave reactor and react at 100 W for 10 min to obtain a composite 4A molecular sieve raw material powder containing silicon carbide radio wave absorbing material.
[0027] S2: Spheroidization 8 kg (dry basis) of the composite 4A molecular sieve raw material powder containing the produced silicon carbide radio wave absorbing material and 2 kg of kaolin were weighed, put into a Φ500 mm mixer, and mixed for 30 minutes to obtain a mix. 5 kg of the mix (based on dry weight) was weighed and placed in an EIRICH automatic molding machine, where it was poured into the mixed solution for molding, and the diameter of the molded particles was adjusted to 1.2-1.8 mm. The molded particles were placed in a vacuum muffle furnace and roasted at 350-550°C for 2-3 hours to obtain a spherical particle material. The spherical particle material was placed in a drying dish, cooled to room temperature, and sampled to measure the static moisture adsorption, which reached 21.7 wt%.
[0028] S3: Crystal transition 3 kg of the spherical particle material was weighed out and placed in deionized water, resulting in a total weight of 4.84 kg. 3 kg of the spherical particle material was added to a sodium hydroxide solution with a concentration of 8% by mass in a weight ratio of 3.5:1 between the obtained crystallization reaction solution and the spherical particle material, thereby obtaining a crystallization reaction solution. The temperature was raised to 95° C., and the solution was placed in a solution bath, where the crystallization reaction was carried out for 3 hours. After the crystallization reaction is completed, the balls are washed with 50L of cold water, then with 10L of 70℃ hot water twice, and further washed with cold water until the pH reaches 8 (measured with test paper), to obtain the crystallization reaction molecular sieve balls. The pH value is sampled and analyzed to reach 10.45. The crystallization reaction molecular sieve balls were tested for water absorption. Test conditions: Absorb water for 24 hours under conditions of 25°C and RH 50. Results: Before the crystallization reaction, it was 21.7 wt%, and after the crystallization reaction, it was 24.5 wt%.
[0029] S4: Lithium ion exchange After the crystal transition, the crystallization reaction molecular sieve ball (4A molecular sieve) was allowed to absorb moisture, placed in a lithium ion exchange device and immersed in water, and the material in the device was heated to 85-90 ° C and kept warm. A lithium sulfate solution with a concentration of 1% by mass to 8% by mass was introduced into the device, and the pH was controlled to 6-12. After a predetermined time, the ion concentration in the liquid was detected from the sampling outlet of the device, and when the ion concentration in the liquid reached a predetermined value, the lithium ion exchange reaction was terminated and an all-zeolite lithium-type molecular sieve was obtained. The all-zeolite lithium-type molecular sieve in the device was rinsed with deionized water, and when it was rinsed to the desired extent, the material was taken out and dehydrated, and the all-zeolite lithium-type molecular sieve was collected.
[0030] S5: Activation The all-zeolite lithium-type molecular sieve was slowly added to the belt oven for pre-baking, the temperature in the oven was controlled at 80-220°C, the moisture content of the material after drying was controlled at 5%-15%, and the material was collected in a container. The dried material was placed in a vertical activation furnace, and pure nitrogen gas or dry compressed air with a dew point of -70°C was heated to 450-600°C by an electric heater. The hot gas was introduced into the vertical activation furnace to heat the material to 500-580°C for roasting, and the material was kept warm for 3-5 hours to obtain the finished product of all-zeolite lithium-type molecular sieve containing silicon carbide radio wave absorbing material. Then, the finished product of all-zeolite lithium type molecular sieve containing radio wave absorbing material in the vertical furnace is cooled to 50℃-20℃ by a cooler, and then sieved under the protection of nitrogen gas or suitable dry air, and packaged in a packaging barrel. The results of testing the finished all-zeolite lithium molecular sieve containing the radio wave absorbing material showed that the static moisture adsorption was 23.6wt%, the Li exchange degree was 96.6%, the bulk density was 0.69g / ml, the wear rate was 0.09wt%, the average particle size was 1.38mm, the sieving particle size (<1.00) was 0.1wt%, the sieving particle size (>1.70) was 0.1wt%, and the water content was 0.952wt%, all of which had excellent properties. The finished product has good sphericity, uniform particle size, and excellent stacking effect, which can be used to remove impurities from the electrolyte of lithium-ion batteries. Example 2
[0031] This embodiment relates to a method for producing an all-zeolite lithium-type molecular sieve, including steps S1 to S4.
[0032] S1: Spheroidization Commercially available 4A molecular sieve (chemical formula: 3Na 2 O:2SiO 2 :Al 2 O 3 :128H 2 O) 8 kg of raw material powder (dry basis) and 2 kg of kaolin were weighed out, placed in a Φ500 mm mixer, and mixed for 30 minutes. 5 kg of the mix was weighed and placed in an EIRICH automatic molding machine, and the mixed solution was injected for molding, and the diameter of the molded particles was 1.2-1.8 mm. The molded particles were placed in a vacuum muffle furnace and roasted at 350-550°C for 2-3 hours to obtain a spherical particle material. The spherical particle material was placed in a drying dish, cooled to room temperature, and sampled to measure the static moisture adsorption, which reached 20.0 wt%.
[0033] S2: Crystal transition 3 kg of the spherical particle material was added to a sodium hydroxide solution having a concentration of 8% by mass so that the weight ratio of the obtained crystallization reaction solution to the spherical particle material was 3.5:1, thereby obtaining a crystallization reaction solution. The temperature was raised to 95° C., and the solution was placed in a solution bath, where the crystallization reaction was carried out for 3 hours. After the crystallization reaction is completed, the balls are washed with 50L of cold water, then with 10L of 70℃ hot water twice, and further washed with cold water until the pH is 8 (measured with test paper), to obtain the crystallization reaction molecular sieve balls. The pH value is sampled and analyzed to reach 10.45. The crystallization reaction molecular sieve balls were tested for water absorption. Test conditions: Water absorption for 24 hours under conditions of 25°C and RH 50. Results: Water absorption was 20.0wt% before the crystallization reaction and 22.3wt% after the crystallization reaction.
[0034] S3: Lithium ion exchange After the crystal transition, the crystallization reaction molecular sieve ball (4A molecular sieve) was allowed to absorb moisture, placed in a lithium ion exchange device and immersed in water, and the material in the device was heated to 85-90 ° C and kept warm. A lithium sulfate solution with a concentration of 1% by mass to 8% by mass was introduced into the device, and the pH was controlled to 6-12. After a predetermined time, the ion concentration in the liquid was detected from the sampling outlet of the device, and when the ion concentration in the liquid reached a predetermined value, the lithium ion exchange reaction was terminated and an all-zeolite lithium-type molecular sieve was obtained. The all-zeolite lithium-type molecular sieve in the device was rinsed with deionized water, and when it was rinsed to the desired extent, the material was taken out and dehydrated, and the all-zeolite lithium-type molecular sieve was collected.
[0035] S4: Activation The all-zeolite lithium-type molecular sieve was slowly added to the belt oven for pre-baking, the temperature in the oven was controlled at 80-220°C, the moisture content of the material after drying was controlled at 5%-15%, and the material was collected in a container. The dried material was placed in a vertical activation furnace, and pure nitrogen gas or dry compressed air with a dew point of -70°C was heated to 450-600°C by an electric heater. The hot gas was introduced into the vertical activation furnace to heat the material to 500-580°C for roasting, and the material was kept warm for 3-5 hours to obtain the finished all-zeolite lithium molecular sieve. Then, the finished product of all-zeolite lithium type molecular sieve containing radio wave absorbing material in the vertical furnace is cooled to 20℃-50℃ by a cooler, and then sieved under the protection of nitrogen gas or suitable dry air, and packaged in a packaging barrel. The results of testing the manufactured finished product showed that the static moisture adsorption was 22.5wt%, the Li exchange degree was 94.0%, the bulk density was 0.70g / ml, the wear rate was 0.15wt%, the average particle size was 1.34mm, the sieving particle size (<1.00) was 0.5wt%, the sieving particle size (>1.70) was 0.5wt%, and the moisture content was 0.952wt%, which are excellent in properties. The finished product has good sphericity, uniform particle size, and excellent stacking effect, which can be used to remove impurities from the electrolyte of lithium-ion batteries. Example 3
[0036] This embodiment relates to a method for producing an all-zeolite calcium type molecular sieve containing a radio wave absorbing material, which includes steps S1 to S5.
[0037] S1: In situ synthesis of composite A-type molecular sieve raw powder with radio wave absorbing function Molar ratio of materials: 12M 2 O:60SiO 2 :Al 2 O 3 :400H 2 In O, sodium silicate was weighed and mixed uniformly with water to prepare a solution, and tetramethylammonium hydroxide solution was weighed and added to aluminum isopropoxide and sodium hydroxide to prepare a solution. The two solutions were mixed uniformly, and the molar ratio of tetramethylammonium hydroxide (TMA) to sodium ions in the mixed solution was set to 1.675. Weigh out 0.5 kg of silicon carbide powder, add it to the alkaline silica aluminosol reaction liquid (added according to the theoretical yield of 9.5 kg of A-type molecular sieve), and place it in a microwave reactor and react at 100 W for 60 min to obtain a composite 4A molecular sieve raw material powder containing silicon carbide radio wave absorbing material.
[0038] S2: Spheroidization 9 kg (dry basis) of the composite 4A molecular sieve raw material powder containing the produced silicon carbide radio wave absorbing material and 1 kg of halloysite were weighed out, put into a Φ500 mm mixer, and mixed for 30 minutes. 5 kg of the mix (calculated as dry basis weight) was weighed out and placed in an EIRICH automatic molding machine, and the mixed solution was injected for molding, resulting in molded particles with a diameter of 1.2 to 1.8 mm. The shaped particle material was placed in a vacuum muffle furnace and roasted at 350 to 550° C. for 2 to 3 hours to obtain a spherical particle material. The spherical particle material was placed in a drying dish, cooled to room temperature, and sampled to measure the static moisture adsorption, which reached 25.2 wt%.
[0039] S3: Crystal transition 3 kg of the spherical particle material was added to a sodium hydroxide solution having a concentration of 8% by mass so that the weight ratio of the obtained crystallization reaction solution to the spherical particle material was 3.5:2, thereby obtaining a crystallization reaction solution. The temperature was raised to 95° C., and the solution was placed in a solution bath, where the crystallization reaction was carried out for 3 hours. After the crystallization reaction is completed, the balls are washed with 50L of cold water, then with 10L of 70℃ hot water twice, and further washed with cold water until the pH is 8 (measured with test paper), to obtain the crystallization reaction molecular sieve balls. The pH value is sampled and analyzed to reach 10.45. The crystallization reaction molecular sieve balls were tested for water absorption. Test conditions: Water absorption for 24 hours under conditions of 25°C and RH 50. Results: Water absorption was 25.2wt% before the crystallization reaction and 28.0wt% after the crystallization reaction.
[0040] S4: Calcium ion exchange After the crystal transition, the crystallization reaction molecular sieve ball (4A molecular sieve) was allowed to absorb moisture, placed in a lithium ion exchange device and immersed in water, and the material in the device was heated to 85-90 ° C and kept warm. A calcium chloride solution with a concentration of 2% by mass to 10% by mass was introduced into the device, and the pH was controlled to 6-9. After a predetermined time, the ion concentration in the liquid was detected from the sampling outlet of the device, and when the ion concentration in the liquid reached a predetermined value, the calcium ion exchange reaction was terminated to obtain an all-zeolite calcium type molecular sieve (5A molecular sieve). The all-zeolite calcium type molecular sieve in the device was rinsed with deionized water, and when it was rinsed to the desired extent, the material was taken out and dehydrated, and the all-zeolite calcium type molecular sieve was collected.
[0041] S5: Activation The all-zeolite calcium type molecular sieve was slowly added to the belt oven for pre-baking, the temperature in the oven was controlled at 80-220°C, the moisture of the material after drying was controlled at 5%-15%, and the material was collected in a container. The dried material was placed in a vertical activation furnace, and pure nitrogen gas or dry compressed air with a dew point of -70°C was heated to 450-600°C by an electric heater. The hot gas was introduced into the vertical activation furnace, and the material was heated to 500-580°C for roasting, and kept warm for 3-5 hours to obtain the finished all-zeolite calcium molecular sieve containing the radio wave absorbing material. Then, the temperature of the all-zeolite calcium molecular sieve containing the radio wave absorbing material in the vertical furnace is lowered to 50℃ to 20℃ by a cooler, and the finished product is sieved under the protection of nitrogen gas or suitable dry air, and then packaged in a packaging barrel. The results of testing the finished product showed that the static moisture adsorption was 24.1wt%, the calcium ion exchange rate was 95.2%, the bulk density was 0.69g / ml, the wear rate was 0.07wt%, the average particle size was 1.31mm, the sieving particle size (<1.00) was 0.4wt%, the sieving particle size (>1.70) was 0.3wt%, and the moisture content was 0.952wt%, all of which have excellent properties. The finished product has good sphericity, uniform particle size, and excellent stacking effect, which can be used to remove impurities from the electrolyte of lithium-ion batteries. Example 4
[0042] This embodiment relates to a method for producing an all-calcium zeolite type molecular sieve, including steps S1 to S4.
[0043] S1: Spheroidization Commercially available 4A molecular sieve (chemical formula: 12M 2 O 60SiO 2 ·Al 2 O 3 400H 2 9 kg of raw material powder (O, M: tetramethylammonium ion) (dry basis) and 1 kg of halloysite were weighed out and placed in a Φ500 mm mixer and mixed for 30 minutes. 5 kg of the mix (calculated as dry basis weight) was weighed out and placed in an EIRICH automatic molding machine, and the mixed solution was injected for molding, resulting in molded particles with a diameter of 1.2 to 1.8 mm. The molded particles were placed in a vacuum muffle furnace and roasted at 350-550°C for 2-3 hours to obtain a spherical particle material. The spherical particle material was placed in a drying dish, cooled to room temperature, and sampled to measure the static moisture adsorption, which reached 22.7 wt%.
[0044] S2: Crystal transition 3 kg of the spherical particle material was added to a sodium hydroxide solution having a concentration of 8% by mass so that the weight ratio of the obtained crystallization reaction solution to the spherical particle material was 3.5:2, thereby obtaining a crystallization reaction solution. The temperature was raised to 95° C., and the solution was placed in a solution bath, where the crystallization reaction was carried out for 3 hours. After the crystallization reaction is completed, first wash with 50L of cold water, then wash with 10L of 70℃ hot water twice, and then wash with cold water until the pH is 8 (measured by test paper). The crystallization reaction molecular sieve ball is obtained, and the pH value is sampled and analyzed, which reaches 10.45. The crystallization reaction molecular sieve balls were tested for water absorption. Test conditions: Water absorption for 24 hours under conditions of 25°C and RH 50. Results: Water absorption was 22.7wt% before the crystallization reaction, and 25.2wt% after the crystallization reaction.
[0045] S3: Calcium ion exchange After the crystal transition, the crystallization reaction molecular sieve ball (4A molecular sieve) was allowed to absorb moisture, placed in a lithium ion exchange device and immersed in water, and the material in the device was heated to 85-90 ° C and kept warm. A calcium chloride solution with a concentration of 2-10 mass% was introduced into the device, and the pH was controlled to 6-9. After a predetermined time, the ion concentration in the liquid was detected from the sampling outlet of the device, and when the ion concentration in the liquid reached a predetermined value, the calcium ion exchange reaction was terminated to obtain an all-zeolite calcium type molecular sieve (5A molecular sieve). The all-zeolite calcium type molecular sieve in the device was rinsed with deionized water, and when it was rinsed to the desired extent, the material was taken out and dehydrated, and the all-zeolite calcium type molecular sieve was collected.
[0046] S4: Activation The all-zeolite calcium type molecular sieve was slowly added to the belt oven for pre-baking, the temperature in the oven was controlled at 80-220°C, the moisture of the material after drying was controlled at 5%-15%, and the material was collected in a container. The dried material was placed in a vertical activation furnace, and pure nitrogen gas or dry compressed air with a dew point of -70°C was heated to 450-600°C by an electric heater. The hot gas was introduced into the vertical activation furnace, and the material was heated to 500-580°C for roasting, and kept warm for 3-5 hours to obtain the finished all-calcium zeolite molecular sieve. Then, the temperature of the all-zeolite calcium molecular sieve finished product in the vertical furnace is lowered to 50℃-20℃ by a cooler, and then it is sieved under the protection of nitrogen gas or suitable dry air, and packaged in a packaging barrel. The results of testing the finished product showed that the static moisture adsorption was 22.1wt%, the calcium ion exchange rate was 94.3%, the bulk density was 0.69g / ml, the wear rate was 0.07wt%, the average particle size was 1.31mm, the sieving particle size (<1.00) was 0.4wt%, the sieving particle size (>1.70) was 0.3wt%, and the moisture content was 0.952wt%, all of which have excellent properties. The finished product has good sphericity, uniform particle size, and excellent stacking effect, which can be used to remove impurities from the electrolyte of lithium-ion batteries. After the molecular sieve adsorbs water in the electrolyte until it is saturated or the adsorption capacity drops to a predetermined value, the molecular sieve is washed, and then the water-adsorbed molecular sieve is dehydrated and regenerated by the microwave high-temperature activation process of the present invention, thereby recovering the adsorption capacity of the molecular sieve and realizing the recycling of the molecular sieve.
[0047] As a result of comparing Examples 1-2 and Examples 3-4, it is found that the all-zeolite molecular sieve can be produced by subjecting a normal commercially available A-type molecular sieve to spheroidization, crystallization, crystal transition, and activation processes, and can be used to remove impurities from a lithium ion non-aqueous electrolyte. However, in Examples 1 and 3, the composite A-type molecular sieve raw material powder is synthesized by microwave heating, so the reaction is efficient and the energy consumption is low. As a result, the all-zeolite molecular sieve containing the radio wave absorbing material produced thereby has further improved static moisture adsorption characteristics and the like.
[0048] The all-zeolite molecular sieves produced in Examples 2 and 4 were allowed to absorb water for 24 hours under conditions of 25°C and RH50, and then placed in an oven to desorb and regenerate. They were baked at 150°C for 2 hours, the oven power was set to 2 kW, the moisture content was reduced to 10% or less, and the estimated power consumption was 4 kW·h. When the moisture content was reduced to 10% by microwave heating, the microwave power was 1 kW, the time required was 1 hour, and the estimated power consumption was 1 kW·h.
[0049] The all-zeolite molecular sieves containing the radio wave absorbing materials produced in Examples 1 and 3 were allowed to absorb water for 24 hours under conditions of 25°C and RH50, and then placed in a microwave heater to desorb and regenerate. The microwave was turned on for 30 minutes, the power was set to 1 kW, and the water content was reduced to 10% or less, and the estimated power consumption was 0.5 kW·h.
[0050] As described above, the all-zeolite molecular sieve containing the radio wave absorption material produced in Example 1 and Example 3 is activated and regenerated by microwave heating, so that the molecular sieve can be efficiently recycled, and the energy consumption and cost can be significantly reduced.
[0051] It should be noted that the above is merely a preferred embodiment of the present invention, and does not limit the present invention in any way. Simple modifications, equivalent changes and modifications made to the above embodiments based on the technical spirit of the present invention are included in the scope of the technical solutions of the present invention.
Claims
1. A method for producing a composite A-type molecular sieve raw material powder containing an electromagnetic wave absorbing material, comprising the steps of: Weigh out the radio wave absorbing material powder having a size of 1 nm to 100 μm, add it to the A-type molecular sieve precursor reaction solution, and then heat it with microwaves to react with it; When heated by microwaves, the radio wave absorbing material is selectively heated, and the molecular sieve grows in situ as a crystal seed for growing the molecular sieve due to the effect of the particle surface, synthesizing the A-type molecular sieve, and the synthesized A-type molecular sieve covers the radio wave absorbing material; After the reaction is completed, the mixture is dried to obtain a composite A-type molecular sieve raw material powder containing the radio wave absorbing material. The A-type molecular sieve precursor reaction solution is an alkaline silica aluminum reaction solution. A manufacturing method comprising the steps of:
2. The alkaline silica aluminum reaction solution has a molar ratio of xM 2 O:ySiO 2 :Al 2 O 3 :zH 2 O (wherein M is one or more of an alkali metal ion and an organic ammonium ion, x is 2 to 12, y is 1.5 to 6.5, and z is 30 to 400), The microwave heating output power is 0.1-2 kW, the reaction temperature is 40-110°C, and the drying temperature is 80-120°C. The method of claim 1 .
3. The radio wave absorbing material includes one or more of silicon carbide particles, silicon carbide fibers, carbon fibers, graphene, carbon nanotubes, and carbon black, and the A-type molecular sieve is an LTA-type molecular sieve. The method of claim 1 .
4. The size of the radio wave absorbing material is 10 nm to 10 μm. The method of claim 1 .
5. A composite A-type molecular sieve raw material powder containing an electromagnetic wave absorbing material, A radio wave absorbing material manufactured by the manufacturing method according to any one of claims 1 to 4, the radio wave absorbing material having a size of 1 nm to 100 μm, and an A-type molecular sieve grown in situ using the radio wave absorbing material as a crystal seed, the A-type molecular sieve covering the radio wave absorbing material.
1. A composite type A molecular sieve raw material powder comprising:
Citation Information
Patent Citations
Method for preparing LiLSX molecular screen
CN101289196A
Preparation method of high dielectric composite mesoporous molecular sieve catalyst
CN109261195A
X-type zeolite molded body and its production
JP1991295805A
Binderless 3a type zeolite bead adsorbent and method of manufacturing for the same as well as adsorption and removal method using the same
JP2002119849A
Method of treating surface of glass
JP2005145807A